Analisis Efisiensi Pemasaran Ikan Tuna Segar Di Kabupaten Pacitan - Azizun Zuhudatin Na’im; Darsono Darsono; Setyowati Setyowati (Universitas Sebelas Maret, 2018)
This study aims to determine the pattern of marketing channels, the role and function of marketing agencies, cost, profit, marketing margins, as well as examine the most economically efficient fresh tuna fish marketing channels in Pacitan. The research location is in Pelabuhan Perikanan Pantai (PPP) Tamperan Pacitan. Methods of sample selection was accidental sampling for fishermen and snowball sampling for marketing agencies. The results showed that (1) there are three marketing channels of fresh tuna, namely, the Marketing channel I (fisherman- collector- retailer- household consumers), the channel II (fisherman-collector- industrial consumers in the city) channel III (fishermen – collector – wholesalers). (2) collector has exchange function and physical function, wholesalers have an exchange function, physical function and function facilities, while retailers have exchange function and physical function. (3) In the first line the total cost of Rp 1.3.14,83 / kg, the total profit of Rp 4685.17 / kg, total marketing margin of Rp 6000.00 / kg and the farmer's share of 71.43%. total cost marketing of channel II is Rp 2195.75 / kg, the total profit of Rp 2804.25 / kg, the total margin is Rp 5000.00 / kg and the farmer's share of 83.33%. total cost marketing channel III is Rp 7.455 90 / kg, the total profit of Rp 3544.10 / kg, total marketing margin is Rp 11,000 / kg and the farmer's share of78.43%. (4) Channel II is the most efficient channel economically with farmer's percentage share of 83.33%.